Aortic Dissection: Simulation Tools for Disease Management and Understanding - Alimohammadi, Mona (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2018)
This thesis addresses computation fluid dynamics modelling of aortic dissection (AD), in order to generate in silico diagnostic information and assess 'virtual surgery' outcomes. The thesis introduces several important advances in the modelling of aortic dissection and lays essential groundwork for further development of this technology. The work thesis represents a unique and major step forward in our understanding of AD using a patient-specific, systematic and coherent simulation approach, and is currently the most advanced work available on AD. .